Participation and deliberation: a case study of readers’ comments to news stories on the Brazilian presidential campaign - Silva, Marisa Torres da (2013)
The Internet has created new “dialogical spaces” (Oblak, 2005) where issues of common concern can be discussed, serving to democratize the public sphere. As a potential deliberative section and a civic forum, readers’ comments in newspapers’ websites constitute a locus for public debate and ideas exchange provided by the mainstream media. As a case study, this article intends to assess the quality of audience participation in online news sites, by analysing the readers’ comments in the news about the Brazilian presidential campaign (September-November 2010) in the online versions of two Portuguese newspapers.